(untitled) (Groundings Undergraduate, 2024)
The commercialisation of festivals can be clearly observed around the world and the term “festivalisation” has been coined to suggest an over-commodification of festivals exploited by tourism and place marketers. While this has attracted a substantial amount of academic work, not many works have focused on Islamic observances like the holy month of Ramadan, particularly in India. In this context, this paper seeks to explore the varying expressions and significations of Ramadan in modern-day Hyderabad, an Indian metropolis whose history is rooted in Islamic tradition. In-depth interviews were conducted with eight participants from different age groups and social strata, seeking anecdotes and experiences about the observation and/or celebration of Ramadan and Eid-ul-Fitr in Hyderabad. Responses were then broadly thematised to bring out the following major points of discussion: first, the multiple interpretations of the Islamic month within the Muslim community, namely variances in Ramadan culture among Islamic sub-communities; secondly, class differences in celebration of Ramadan among cosmopolitan groups; third, gendered notions about Islamic festivities, and lastly, indulgence in pleasure and public display of religiosity through Ramadan. This revealed the dynamic shades that Ramadan has taken on within the culture of Hyderabad City.